Needs satisfaction and Online Self-Regulated Learning among chinese undergraduates - Xiaohua Zhou; Ching-Sing Chai; Morris Siu-Yung Jong; Huiya Feng (PLoS ONE, 2025)
The increasing popularity of online courses has highlighted the importance of online self-regulated learning (OSRL). However, its use among undergraduates remains challenging. Based on self-determination theory, this study examined whether satisfying three basic psychological needs (i.e., autonomy, competence, and relatedness) could foster the engagement of Chinese undergraduates (N = 381) in OSRL. Data were collected from an online questionnaire, which included a revised Online Self-Regulated Learning Questionnaire, a scale to measure need satisfaction, and demographic information items. Descriptive analyses, confirmatory factor analyses and structural equation modeling were conducted. The results revealed that overall need satisfaction was positively associated with the use of OSRL strategies. Specifically, satisfying autonomy was positively associated with the use of resource management strategies. Feeling competent was positively associated with most OSRL strategies, except for time management and help seeking. A sense of relatedness was positively associated with self-evaluation, task strategies, and help seeking. These findings underscore the unique role of each need in promoting OSRL. Therefore, designers and instructors of online courses should cater to the specific needs of undergraduates to enhance their use of targeted OSRL strategy(ies).